Websites as support tools for learning the English language - Maridueña Macancela, Jacqueline (Journal of Science and Research, 2019)
The Websites contribute much to the learning of the English language, facilitating the teaching of the teachers through the use of dynamic strategies they help to reinforce the cognitive approach with greater ease, since it allows to develop the language skills with precision, improving the communication of the students in the classroom, which separates the ambiguous strategies used with the traditional method of learning. These technological tools are important in the variety of interactive activities and practices for understanding the English language, improving the motivation of students in the improvement of the activities of the subject. According to the results of this research, it was possible to show the change in behavior and assimilation, in such a way that 78% of the students who received the subject of English with the contribution of the Web sites, which allowed them to learn more satisfactory since they had interactive activities for their benefit. The quantitative and qualitative methods of observation were applied, taking as sample 144 students from modules 1, 2, 3 and 4 of English, using a survey of 10 questions oriented to the use of Websites as a support tool for the learning the English language, which is a contribution of great importance for both students and teachers in the interlearning of this foreign language.